HUBUNGAN SOSIAL EKONOMI KELUARGA DENGAN KEJADIAN STUNTING - Ginting, Nabilla Syafirah Br.; Triawanti, Triawanti; Juhairina, Juhairina (Universitas Lambung Mangkurat, 2024)
Abstract: Stunting is a chronic malnutrition problem caused by insufficient nutritional intake over a long period of time due to the provision of food that does not meet nutritional needs. Stunting can be measured with a Z-Score limit of <- 2 SD to - 3 SD (short) and <- 3 SD (very short). This research aims to determine the relationship between socio-economics and the incidence of stunting. This research was carried out observationally with a case control approach. A total of 168 maternal subjects who had stunted and non-stunting children were selected based on inclusion and exclusion criteria. The results of the chi-square test showed that there was a relationship between income and family responsibilities and stunting (p = 0.047, p = 0.030) while there was no relationship between maternal education and employment with the incidence of stunting (p = 0.114, p = 0.174). This research concludes that income and family responsibilities are related to the incidence of stunting, while maternal education and employment are not related to the incidence of stunting Keywords: Stunting, income, mother's education, employment, family responsibilities Abstrak: Stunting adalah masalah kurang gizi kronis yang disebabkan oleh asupan gizi yang kurang dalam waktu cukup lama akibat pemberian makanan yang tidak sesuai dengan kebutuhan gizi. Stunting dapat diukur dengan batas Z-Score <- 2 SD sampai dengan- 3 SD (pendek) dan <- 3 SD (sangat pendek). Penelitian ini bertujuan untuk mengetahui hubungan antara sosial ekonomi dengan kejadian stunting. Penelitian ini dilakukan melalui observasional dengan pendekatan case control. Sebanyak 168 subjek ibu yang memiliki anak stunting dan tidak stunting dipilih berdasarkan kriteria inklusi dan eksklusi. Hasil uji chi-square menunjukkan bahwa terdapat hubungan antara penghasilan dan tanggungan keluarga dengan stunting (p = 0,047, p = 0,030) sedangkan pada pendidikan ibu dan pekerjaan tidak didapatkan hubungan dengan kejadian stunting (p = 0,114, p = 0,174). Penelitian ini menyimpulkan bahwa penghasilan dan tanggungan keluarga berhubungan dengan kejadian stunting, sedangkan pendidikan ibu dan pekerjaan tidak berhubungan dengan kejadian stunting. Kata-kata kunci: Stunting, penghasilan, pendidikan ibu, pekerjaan, tanggungan keluarga